2019
DOI: 10.5194/deuquasp-2-69-2019
|View full text |Cite
|
Sign up to set email alerts
|

The Bronze Age battlefield in the Tollense Valley – conflict archaeology and Holocene landscape reconstruction

Abstract: Abstract. Archaeological discoveries in the Tollense Valley represent remains of a Bronze Age battle of ca. 1300–1250 BCE, documenting a violent group conflict hitherto unimagined for this period of time in Europe, changing the perception of the Bronze Age. Geoscientific, geoarchaeological and palaeobotanical investigations have reconstructed a tree- and shrubless mire characterised by sedges, reed and semiaquatic conditions with a shallow but wide river Tollense for the Bronze Age. The exact river course cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The assumed starting point of the battle is a pathway currently overgrown by peat, which crossed the river and surrounding mire (Jantzen et al, 2014). Results of archaeological excavations and interdisciplinary research on the found materials, as well as geoscientific results on the Bronze Age palaeoenvironment, are presented in Brinker et al (2018), Flohr et al (2015), Krüger et al (2012), , Price et al (2017), and Lidke and Lorenz (2019).…”
Section: Areas Of Specific Interest and Ongoing Researchmentioning
confidence: 99%
“…The assumed starting point of the battle is a pathway currently overgrown by peat, which crossed the river and surrounding mire (Jantzen et al, 2014). Results of archaeological excavations and interdisciplinary research on the found materials, as well as geoscientific results on the Bronze Age palaeoenvironment, are presented in Brinker et al (2018), Flohr et al (2015), Krüger et al (2012), , Price et al (2017), and Lidke and Lorenz (2019).…”
Section: Areas Of Specific Interest and Ongoing Researchmentioning
confidence: 99%
“…In case of humans O isotope composition was measured in single samples of enamel, except the individual from Kowal, for whom enamel, dentin and bones samples were analysed. Location of Tollense after[145], simplified.…”
mentioning
confidence: 99%